2020
DOI: 10.1038/s41598-020-69061-4
|View full text |Cite
|
Sign up to set email alerts
|

11-Deoxycortisol controls hydromineral balance in the most basal osmoregulating vertebrate, sea lamprey (Petromyzon marinus)

Abstract: It is unknown whether and how osmoregulation is controlled by corticosteroid signaling in the phylogenetically basal vertebrate group Agnatha, including lampreys and hagfishes. It is known that a truncated steroid biosynthetic pathway in lampreys produces two predominant circulating corticosteroids, 11-deoxycortisol (S) and 11-deoxycorticosterone (DOC). Furthermore, lampreys express only a single, ancestral corticosteroid receptor (CR). Whether S and/or DOC interact with the CR to control osmoregulation in lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
1
24
2
Order By: Relevance
“…Sequence analysis revealed that the MR and GR are kin (9,13). A distinct GR and MR rst appear in cartilaginous sh, which occupy a key position at an ancestral node from which ray-nned sh and terrestrial vertebrates diverged (14,49,50). Genomic analyses reveal that elephant shark genes are evolving slowly (14).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis revealed that the MR and GR are kin (9,13). A distinct GR and MR rst appear in cartilaginous sh, which occupy a key position at an ancestral node from which ray-nned sh and terrestrial vertebrates diverged (14,49,50). Genomic analyses reveal that elephant shark genes are evolving slowly (14).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of migrating to the ocean, Lake Michigan and Lake Champlain sea lamprey spend their entire life in freshwater and never acclimate to salt water environments. Previous work has shown that 11-deoxycortisol, Na-K-Cl cotransporter 1, and Na + -K + -ATPase may engage in sea lamprey’s osmoregulation [ 53 55 ]. We would expect to detect genetic differentiation at genes encoding these components involved in osmoregulation, but we did not find any direct evidence at the genetic level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxycorticosterone is a type of steroid hormone possessing activities of the mineralocorticoid and serves as the precursor of aldosterone. It is involved in water and salt metabolism, playing an important role in electrolyte balance and in the volume of body fluid [32]. It has been reported that deoxycorticosterone and its derivatives-neurosteroids transformed in the fetal brain-protect the central nervous system.…”
Section: Discussionmentioning
confidence: 99%